Guidelines for in vitro simulated digestion and absorption of food - Meili Xin; Min Zhao; Jinlong Tian; Bin Li (Food Frontiers, 2023)
Abstract With the continuous improvement of people's living standards, food intake, bioactivity, and bioavailability have mainly concerned people. Therefore, the digestion and absorption of this kind of food have attracted people's attention. Some food has very high nutritional, medicinal, and medical value. However, because of its low conversion rate and utilization rate, the human body digests and absorbs less material, so the use of human value will be significantly reduced. Therefore, simulation and testing of digestion and absorption in vitro may be significant for dietary intake of bioactive substances. This paper reviews the organs and pathways of simulated food digestion and absorption in vitro and specific processing methods. In an in the vitro simulation system, the role of the human digestive system and absorption system in food digestion and absorption is described, and the performance of various simulation models, exceptionally dynamic in vitro models, is compared. Widespread use and refinement of these models will expand our understanding of the complex interplay of food substrates and digestive and absorptive systems. Therefore, it will be possible to design food with better bioavailability, more benefits to human health, and more targeted delivery, which is also in line with the development trend of food in the future.